A novel BEA-type zeolite core–shell multiple catalyst for hydrogen-rich gas production from ethanol steam reforming. Issue 14 (5th April 2016) - Zheng, Ziliang; Yang, Donghua; Li, Tingting; Yin, Xuemei; Wang, Shiyao; Wu, Xu; An, Xia; Xie, Xianmei
Abstract : BEA-type core–shell catalysts consisting of a core supporting Cu and Fe and a Ni-based shell were investigated for their ethanol steam reforming (ESR) activity. Abstract : BEA-type core–shell catalysts consisting of a core supporting Cu and Fe and a Ni-based shell were investigated for their ethanol steam reforming (ESR) activity. The effect of the nature of the core–shell double-support and the promotion achieved by adding Ni, Cu and Fe were studied. The catalysts were characterized by XRD, BET, SEM, TEM, H2 -TPR, CH4 -TPD, CO-TPD and XAFS analyses. Compared to zeolite Beta as support, the core–shell catalysts exhibited excellent performance in ethanol reforming, leading to high selectivity to hydrogen through a multiple reaction system. This result indicated that the special structural advantages of the core–shell support could give full play to the properties of active phases and provide a one-step production process for high-purity hydrogen. The Ni-base shell was twice as active for the catalytic reaction, resulting in greatly improved catalytic activity and selectivity to hydrogen; in addition, the decrease of by-products could be attributed to the function of the Cu and Fe phases, improving the steam acetaldehyde reforming, steam methane reforming and water gas shift reactions. Furthermore, in the investigation of the effects of the amount of the Cu and Fe phases, the best catalytic performance was reported by the 2.5Fe2.5Cu-SB@NB catalyst.